Francisco Javier DÍEZ DE REVENGA.— Carmen Conde, desde su edén. Murcia: Real Academia Alfonso X El Sabio, 2020, 333 pp. (Susana M.ª Teruel Martínez) - TERUEL MARTÍNEZ, Susana M. (Signa: Revista de la Asociación Española de Semiótica, 2022)